Analisis Pengembangan Pendidikan Nilai-Nilai Karakter Berbasis Tri Hita Karana dengan Pendekatan Kontekstual dalam Pembelajaran Matematika - Moh. Supratman; Made Sutajaya; Wayan Suja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The goal of this study is to look at and explain how character education based on Tri Hita Karana and a contextual approach to learning math has changed over time. This study is a review of the literature. For this research to work, there needs to be a way to get data from reading sources like journals, books, articles, and so on. What the research showed. With a context-based approach, character education based on Tri Hita Karana can be incorporated into the process of learning math. Character education based on THK can be done through activities in the learning process, daily activities at school, co-curricular and extracurricular activities, and daily activities at home and in the community. In conclusion, the use of a contextual approach to develop and improve a student's character can be seen in the learning activities that are done, such as connecting what is being taught to the student's real life at home, at school, and in the community. The goal is for the student to find meaning in the material for his life. Keyword: Tri Hita Karana, Contextual Approach, Learning Mathematics